A Phase I Study Of Oxaliplatin And Doxorubicin In Pediatric Patients With Relapsed Or Refractory Extracranial Non-Hematopoietic Solid Tumors - Mascarenhas, Leo (2013)
BACKGROUND: The combination of a platinum agent and anthracycline has shown activity in pediatric solid tumors. This trial evaluated the maximum tolerated dose (MTD) and dose limiting toxicities (DLT) of oxaliplatin combined with doxorubicin in pediatric patients with recurrent solid tumors. METHODS: Oxaliplatin was administered on day 1 and Doxorubicin on days 1–3 of each 21 day course. The study utilized a standard 3 + 3 dose escalation design. Three dose levels were evaluated: 1) oxaliplatin 105 mg/m(2) and doxorubicin 20 mg/m(2), 2) oxaliplatin 130 mg/m(2) and doxorubicin 20 mg/m(2), and 3) oxaliplatin 130 mg/m(2) and doxorubicin 25 mg/m(2). Dexrazoxane was administered at 10 times the doxorubicin dose prior to doxorubicin infusion. RESULTS: Seventeen patients were enrolled. Dose level 1 was the determined MTD. Grade 2 cardiac DLT was seen in 1 of 6 patients on dose level 1, grade 4 thrombocytopenia in 2 of 5 patients on dose level 2, and 1 each of grade 2 cardiac and grade 4 thrombocytopenia in 5 patients on dose level 3. Cardiac DLT was only noted in patients with prior exposure to both anthracycline and chest radiation. No grade 3 or 4 neurotoxicity or mucositis was seen. Objective responses were noted in 2 patients with neuroblastoma and 1 each of mixed germ cell tumor, thymic neuroendocrine carcinoma and nasopharyngeal carcinoma. CONCLUSIONS: Oxaliplatin 105 mg/m(2) on day 1 combined with doxorubicin 20 mg/m(2) days 1–3 was the MTD. This combination shows sufficient activity to justify further studies in select pediatric tumors.